Image of Islamic Symbols: Modern Malaysian Islamic Art Exhibition Theme - W. Mohamad Daud, Wan Samiati Andriana; Mokhtar, Mumtaz; Sabri, Nik Syahida (Environment-Behaviour Proceedings Journal, 2024)
Symbols can be incorporated into many art forms, including sculpture, photography, and painting. The exhibition is an activity to display a piece of art in the form of goods, services, or achievements to the public. This paper aims to gather information on sculpture that representing Islamic images in Islamic exhibitions from 1957 to 1999. The observation method is used where the artworks have been considered and recorded accordingly, such as the artwork's title, dimension or size, media, and techniques used in producing the artwork. 13 artworks have been identified as artworks that can represent Islamic symbols.